A general solution method for moral hazard problems. Issue 3 (18th October 2018) - Ke, Rongzhu; Ryan, Christopher Thomas
Abstract : Principal–agent models are pervasive in theoretical and applied economics, but their analysis has largely been limited to the "first‐order approach" (FOA), where incentive compatibility is replaced by a first‐order condition. This paper presents a new approach to solving a wide class of principal–agent problems that satisfy the monotone likelihood ratio property but may fail to meet the requirements of the FOA. Our approach solves the problem via tackling a max‐min‐max formulation over agent actions, alternate best responses by the agent, and contracts.